Enhanced Spike-specific, but attenuated Nucleocapsid-specific T cell responses upon SARS-CoV-2 breakthrough versus non-breakthrough infections - Ahmed, Mohamed Ibraheem Mahmoud; Diepers, Paulina; Janke, Christian; Plank, Michael; Eser, Tabea M.; Rubio-Acero, Raquel; Fuchs, Anna; Baranov, Olga; Castelletti, Noemi; Kroidl, Inge; Olbrich, Laura; Bauer, Bernadette; et al. (Frontiers in Immunology, 2022)
SARS-CoV-2 vaccine breakthrough infections frequently occurred even before the emergence of Omicron variants. Yet, relatively little is known about the impact of vaccination on SARS-CoV-2-specific T cell and antibody response dynamics on breakthrough infection. We have therefore studied the dynamics of CD4 and CD8 T cell targeting the vaccine-encoded Spike and the non-encoded Nucleocapsid antigens during breakthrough infections (BTI, n=24) and in unvaccinated control infections (non-BTI, n=30). Subjects with vaccine breakthrough infection had significantly higher CD4 and CD8 T cell responses targeting the vaccine-encoded Spike during the first and third/fourth week after PCR diagnosis compared to non-vaccinated controls, respectively. In contrast, CD4 T cell targeting the non-vaccine encoded Nucleocapsid antigen were of significantly lower magnitude in BTI as compared to non-BTI. Hence, previous vaccination was linked to enhanced T cell and antibody responses targeting the vaccine-encoded Spike antigen, while responses against the non-vaccine encoded Nucleocapsid antigen were significantly attenuated.